The influence of Education, Training, and Motivation on Employee Performance of The Public Relations and Protocol at The Regional Secretariat Soppeng Regency - Ayu, Andi Rasma; B I, Gunawan (STIE AMKOP, 2016)
ABSTRACT This research aims: 1) to analyze the influence of education on employee performance of the public relations and protocol Regional Secretariat Soppeng Regency, 2) to analyze the influence of training on employee performance of the public relations and protocol Regional Secretariat Soppeng Regency, 3) to analyze the influence of motivation on employee performance of the public relations and protocol Regional Secretariat Soppeng Regenc, 4) to analyze the influence of education, training, and motivation simultaneously on employee performance of the public relations and protocol Regional Secretariat Soppeng Regency. This research is located on part of public relations and protocol Regional Secretariat Soppeng Regency. Population in this study is the overall civil servant of Public Relations and Protocol numbered 39 people. Sampling using census method. Analysis of the data in this study using multiple linear regression analysis.. The results showed that: 1) education has positive and significant influence on employee performance of the public relations and protocol Regional Secretariat Soppeng Regency, 2) training has positive and significant influence on employee performance of the public relations and protocol Regional Secretariat Soppeng Regency, 3) motivation has positive and significant influence on employee performance of the public relations and protocol Regional Secretariat Soppeng Regency, 4) education, training and motivation have positive and significant influence on employee performance of the public relations and protocol Regional Secretariat Soppeng Regency. Keywords: Education, Training, Motivation, Employee Performance